THE UTILIZATION OF ANIMATED VIDEO MEDIA IN ARABIC LANGUAGE LEARNING AT AL MAAHIRA INTERNATIONAL ISLAMIC BOARDING SCHOOL MALANG - Yuswandi, Yuswandi; Al Anshory, Abdul Muntaqim; Hasaniyah, Nur (Abjadia : International Journal of Education, 2024)
The advancement of technology in the current era has led most students to prefer watching educational stories on smartphones rather than reading stories in books. This presents a challenge for educators to create technology-based educational videos. The lack of understanding of technology among educators makes learning media less engaging, which can decrease student motivation. This research aims to assist educators in utilizing animated video media to create enjoyable learning experiences for students. The study employs a descriptive qualitative approach, where the researcher seeks to describe the utilization of animated video media in Arabic language learning at Al Maahira International Islamic Boarding School Malang. Data collection techniques include interviews, observations, and documentation. The data is then reduced, compiled, sorted, presented, and concluded. The results of the study indicate that animated videos can attract students' interest, helping them focus on the material taught by the teacher and making it easier to understand the content because students tend to be interested in engaging and visual images. The use of animated videos has its advantages and disadvantages. The advantages include making learning more interesting, increasing student motivation, and providing flexibility. The disadvantages include limited resources and the potential for student dependency. To maximize the use of animated videos, schools need to provide adequate facilities, offer training to teachers, and use animated videos in balance with other teaching methods.